An evaluation of neo-Kaleckian supermultiplier and neo-Goodwinian models: Pseudo-goodwin cycles, external markets and pro-cyclical labour productivity - Brett Fiebiger (Hans-Böckler-Stiftung, Macroeconomic Policy Institute (IMK), Forum for Macroeconomics and Macroeconomic Policies (FMM), 2022)
This paper provides a theoretical and empirical evaluation of neo-Kaleckian supermultiplier and neo-Goodwinian models. The benchmark structuralist and Harrodian neo-Goodwinian models posit a macro economy with only one asset: the capital stock. Demand leakages presuppose that at least one sector is able to realise an excess of revenues over expenditures as a positive accumulation of net financial assets vis-à-vis other sectors. Models with a single real asset-and which assume each sector always has nil net lending/borrowing-provide pseudo explanations of real world economic activity. We show that neo-Kaleckian supermultiplier models with overhead labour can account for the induced nature of capacity investment, a pro-cyclical profit share and stylised net lending/borrowing patterns.
Keywords: B22; B50; E11; E20; E30; O40; 330; Pseudo-Goodwin cycles; External markets; Net lending/borrowing; Overhead labour